2013
DOI: 10.1111/ecc.12084
|View full text |Cite
|
Sign up to set email alerts
|

Secondary primary cancer in patients with head and neck carcinoma: the differences among hypopharyngeal, laryngeal, and other sites of head and neck cancer

Abstract: This paper presents a population-based retrospective cohort study to identify the differences in secondary primary cancer (SPC) among hypopharyngeal, laryngeal, and other sites of head and neck cancer (HNC). Data were collected from the Taiwan National Health Insurance Research Database (NHIRD) for the period 1979-2010. The study cohort comprised 5914 newly diagnosed hypopharyngeal and laryngeal patients from the registry of the Catastrophic Illness Patients Database (CIPD). The comparison cohort comprised 591… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…The hypopharynx, and in particular involvement of the piriform sinus, is a well‐known risk factor for the development of esophageal‐SPTs . The results from the present review also SPTs underlined this.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The hypopharynx, and in particular involvement of the piriform sinus, is a well‐known risk factor for the development of esophageal‐SPTs . The results from the present review also SPTs underlined this.…”
Section: Discussionsupporting
confidence: 65%
“…31 The hypopharynx, and in particular involvement of the piriform sinus, is a well-known risk factor for the development of esophageal-SPTs. [57][58][59][60] The results from the present review also SPTs underlined this. Wang WL et al compared two hypopharyngeal HNSCC cohorts: before and after implementing pretreatment Lugol chromoendoscopy esophagus screening.…”
Section: Discussionsupporting
confidence: 62%
“…With the development of modern cancer care, the incidence of secondary primary tumor increased during the past decades [ 21 ]. In our study, two patients had secondary primary cancers, they referred to undergo 18 F-FES PET/CT in order to predict origin of metastasis; and the results showed that 18 F-FES PET/CT may be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Of 551 patients, they reported that the incidence of double cancer was 26.9%, triple cancer was 6.2%, quadruple cancer was 1.1%, and quintuple cancer was 0.2% [ 12 ]. Liu et al studied the types of second primary malignancies among the patients with head and neck cancer [ 13 ]. The types of second primary malignancy with adjusted hazard ratio (95% confidence interval) were esophageal cancer 3.47 (2.40 to 5.03), prostate cancer 0.94 (0.45 to 1.95), bladder cancer 0.90 (0.39 to 2.10), among others [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al studied the types of second primary malignancies among the patients with head and neck cancer [ 13 ]. The types of second primary malignancy with adjusted hazard ratio (95% confidence interval) were esophageal cancer 3.47 (2.40 to 5.03), prostate cancer 0.94 (0.45 to 1.95), bladder cancer 0.90 (0.39 to 2.10), among others [ 13 ]. Powell et al considered the prognosis of patients with MPMN [ 14 ] by dividing patients with MPMN into synchronous and metachronous cases according to the classification proposed by Moertel [ 3 ].…”
Section: Discussionmentioning
confidence: 99%